Sulfonamide Residue in the Broiler Chicken Circulating in Makassar - Fawwaz, Muammar; Razak, Rais; Tahir, Masdiana; Permatasari, Andi; Amula, Andi Tenri; Seniwati, Seniwati (Pharmaceutical Reports, 2022)
The use of sulfonamide related to drug residual in the product of broiler chicken, like meat and egg. This research aimed to determine the sulfonamides (sulfamerazine, sulfanilamide, and sulfadiazine) on the broiler chicken meat, breast, and egg from the three different slaughterhouses circulating in the City of Makassar. The sample was extracted by acetonitrile and acetone then concentrated. The extract and sulfonamides then analyzed by HPLC method using C18 reverse phased column, UV-Visible detector in the wavelength of 270 nm. The result of study shows that the chromatogram of sample breast and egg has similar retention time with sulfonamides as a standard reference. The breast sample contains sulfamerazine residues, sample B and C contains 0.014 and 0.005 % (w/w), respectively. The egg sample A and D contains sulfadiazine 0.045 and 0.108 % (w/w), respectively. Sample B contains sulfanilamide 0.053 % (w/w). Sample A and B is egg yolk, while sample D is egg whites. Based on the results obtained, this is not suitable for the rules set by JECFA of 0.1 mg/kg (10-5 % w/w) as well as the standard of SNI. It can be concluded that generally broiler chicken breast and egg circulating in the City of Makassar was contaminated by sulfonamide with high concentration.